1995
DOI: 10.1104/pp.108.4.1495
|View full text |Cite
|
Sign up to set email alerts
|

Flowering Responses to Altered Expression of Phytochrome in Mutants and Transgenic Lines of Arabidopsis thaliana (L.) Heynh

Abstract: l h e long-day plant Arabidopsis tbaliana (L.) Heynh. flowers early in response to brief end-of-day (EOD) exposures to far-red light (FR) following a fluorescent short day of 8 h. FR promotion of flowering was nullified by subsequent brief red light (R) EOD exposure, indicating phytochrome involvement. The EOD response to R or FR is a robust measure of phytochrome action. Along with their wild-type (WT) parents, mutants deficient in either phytochrome A or B responded similarly to the EOD treatments. Thus, nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 44 publications
8
61
4
Order By: Relevance
“…The multiple-fold overexpression of cotton PHYE (as well as PHYB in line T 3 -1_7) in PHYA1 RNAi plants might result in increased yield potential, as has been seen in tobacco 15 and potato 16 since PHYE is most closely related to PHYB, both functionally and phylogenetically [1][2][3] . This hypothesis is supported by the observation that both the potato PHYB-overexpressing lines 16 and our cotton PHYA1 RNAi suppression lines showed markedly increased anthocyanin production, particularly close to the time of senescence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The multiple-fold overexpression of cotton PHYE (as well as PHYB in line T 3 -1_7) in PHYA1 RNAi plants might result in increased yield potential, as has been seen in tobacco 15 and potato 16 since PHYE is most closely related to PHYB, both functionally and phylogenetically [1][2][3] . This hypothesis is supported by the observation that both the potato PHYB-overexpressing lines 16 and our cotton PHYA1 RNAi suppression lines showed markedly increased anthocyanin production, particularly close to the time of senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochrome genes play key regulatory roles in a wide range of plant developmental processes [1][2][3] . As such, the manipulation of phytochrome gene function has long been considered as a promising avenue for the modification of economically important traits in crops 13,14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, far-red induction of the homeotic gene Athb-2 is mediated mainly by phytochrome(s) other than PhyA and PhyB (Carabelli et al, 1996). Bagnall et al (1995) suggested the possibility of the involvement of phytochrome(s) other than PhyA and PhyB in the end-of-day far-red response of flowering. It was also reported that the phyA/pkyB double mutant displays an inhibition of petiole elongation accompanied by elongated internodes and an early-flowering response to end-of-day far-red treatment.…”
Section: The Role Of Different Phytochromesmentioning
confidence: 99%
“…The involvement of phytochrome in flowering of Arabidopsis was derived from studies using different R/FR ratios during development (Halliday, Koornneef & Whitelam 1994;Johnson et al 1994), end of day red (EOD R) and far-red (EOD FR) treatments (Bagnall et al 1995), daylength extension with low fluences of FR and R (Bagnall et al 1995), phytochromedeficient mutants (Goto et al 1991;Johnson et al 1994;Reed et at. 1994) and transgenic plants overexpressing phytoehrome proteins (Bagnall et al 1995). From these studies it appears that the low fluenee rate FR-enriehed promotive daylength extension effeet is eaused by phytochrome A (phyA), since phyA mutants do not respond to this treatment (Johnson et al 1994).…”
Section: The Role Of Light Perception In Flowering Of Arabidopsismentioning
confidence: 99%